A Novel Locus (RP24) for X-linked Retinitis Pigmentosa Maps to Xq26-27 - Gieser, Linn (1998)
Two genetic loci, RP2 and RP3, for X-linked retinitis pigmentosa (XLRP) have been localized to Xp11.3-11.23 and Xp21.1, respectively. RP3 appears to account for 70% of XLRP families; however, mutations in the RPGR gene (isolated from the RP3 region) are identified in only 20% of affected families. Close location of XLRP loci at Xp and a lack of unambiguous clinical criteria do not permit assignment of genetic subtype in a majority of XLRP families; nonetheless, in some pedigrees, both RP2 and RP3 could be excluded as the causative locus. We report the mapping of a novel locus, RP24, by haplotype and linkage analysis of a single XLRP pedigree. The RP24 locus was identified at Xq26-27 by genotyping 52 microsatellite markers spanning the entire X chromosome. A maximum LOD score of 4.21 was obtained with DXS8106. Haplotype analysis assigned RP24 within a 23-cM region between the DXS8094 (proximal) and DXS8043 (distal) markers. Other chromosomal regions and known XLRP loci were excluded by obligate recombination events between markers in those regions and the disease locus. Hemizygotes from the RP24 family have early onset of rod photoreceptor dysfunction; cone receptor function is normal at first, but there is progressive loss. Patients at advanced stages show little or no detectable rod or cone function and have clinical hallmarks of typical RP. Mapping of the RP24 locus expands our understanding of the genetic heterogeneity in XLRP and will assist in development of better tools for diagnosis.